Foreseeing is not necessarily the same as intending: And the difference is crucial for patients and their doctors. Issue 7196 (29th May 1999) - Gillon, Raanan
Abstract : Following the acquittal of an English doctor, Dr David Moor, who had given a dying patient a lethal dose of diamorphine, we invited two ethicists to debate the issue at the centre of the case: that of giving a drug with the intention of relieving suffering even though it may hasten death. Professor Raanan Gillon argues that the difference between intending and foreseeing is all important, while Professor Len Doyal argues that the effect of this is to raise the moral character of a clinician above the best interests of his or her patients